Surgical management of giant cell tumor in adolescent by excision or curettage followed by fibular strut graft - Bhaskar Reddy, K. Vijaya; Chary, N. Brahma; Mogili, Chenna K. (International Journal of Research in Orthopaedics, 2021)
Giant cell tumour (GCT) in adolescent is a rare tumour. It commonly occurs in skeletally mature patients aged between 20-40 years. In adults it is seen in epiphyseal region. In patients with intact physis, it arises from the metaphysis. Giant cells are more common in females. It is more common in the ends of long bones of distal end of femur, proximal tibia, and distal radius. 14 cases of surgical management of GCT by excision or curettage in adolescent followed by fibular strut graft. 1 year follow up of all cases of GCT in adolescent treated with excision or curettage followed by fibular strut graft was done. Out of 14 patients, 12 patients did not develop any recurrence of GCT. 2 patient developed recurrence after 6 months. All the patients were able to attain good range of movements 2 months after surgery. GCT in adolescent surgically treated with excision or curettage followed by fibular graft had excellent results in terms of recovery of daily activities, wound healing. Chances of recurrence more in patients treated with curettage and bone grafting.